Markerless motion capture in sport: panacea or Pandora`s box? - Glazier, P. S. (Sports Biomechanics, 2025)
This paper critically appraises the utility of markerless motion capture in the context of skill development and sports performance enhancement. If markerless motion capture is to be useful in a profiling or monitoring capacity, the amount of measurement error needs to be smaller than the amount of movement variability over iterative performance trials. Current evidence suggests that it is unlikely that any existing markerless system satisfies this requirement. The resolution of this issue would, in principle, enable technical errors to be more easily pinpointed and performance variation to be better explained. However, decomposing movement variability into its functional and dysfunctional components is not only a nontrivial undertaking for most practitioners, the practical consequences of doing so are limited because synergies are self-organising entities and any attempt to micro-manage their constituent degrees of freedom will likely have deleterious effects on performance. Biomechanical measurements technologies, including markerless motion capture, may be best used to support search strategies employed by coaches and athletes.